2023
DOI: 10.1186/s12905-023-02500-2
|View full text |Cite
|
Sign up to set email alerts
|

Community and provider perceptions and experiences of cervical cancer screening in Rural Bolivia: a qualitative study

Abstract: Background Despite efforts to increase cervical cancer screening access in rural Bolivia, uptake remains low. Bolivia has one of the highest cervical cancer mortality rates in the Americas. As it redoubles efforts to deliver Universal Health Care, the Bolivian government needs information on the factors constraining cervical cancer screening access and utilization, especially in rural areas. Methods Our qualitative study explored cervical cancer sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…Our findings are similar to most of the previous studies that indicate that health workers educating HIV-infected women on HPV testing and CC screening increases the chance of routinely conducting HPV self-sampling among HIV-infected women [44,45]. Previous studies have indicated that HIVinfected have varying perceptions and norms [46], and prefer receiving information on HPV or CC status from healthcare providers because of perceived early diagnosis, prevention, and treatment of disease [47]. Therefore, in addition to the HPV self-sampling approaches health workers should be invited to participate in educating HIV-infected women on HPV as well as collecting the HPV samples [48].…”
Section: Effectiveness Of the Clinic-based Compared To Home-based Hpv...supporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are similar to most of the previous studies that indicate that health workers educating HIV-infected women on HPV testing and CC screening increases the chance of routinely conducting HPV self-sampling among HIV-infected women [44,45]. Previous studies have indicated that HIVinfected have varying perceptions and norms [46], and prefer receiving information on HPV or CC status from healthcare providers because of perceived early diagnosis, prevention, and treatment of disease [47]. Therefore, in addition to the HPV self-sampling approaches health workers should be invited to participate in educating HIV-infected women on HPV as well as collecting the HPV samples [48].…”
Section: Effectiveness Of the Clinic-based Compared To Home-based Hpv...supporting
confidence: 89%
“…Long distance from the access point at the HIV clinic and the CLP location is a significant barrier to HPV self-sampling. Our findings are like previous studies which have assessed distance as a blockage to HPV self-sampling among HIV-infected women [21,33,37,40,47,49,50]. Therefore, there is a need to improve the CLP program which would create demand for HPV self-sampling in preferred places for HPV self-sampling among HIV-infected women.…”
Section: Effectiveness Of the Clinic-based Compared To Home-based Hpv...supporting
confidence: 82%